Rock slope stability assessment based on the critical failure state curve for the generalized Hoek‒Brown criterion - Zhang, Wenlian; Sun, Xiaoyun; Yuan, Wei; Liu, Ting; Jin, Shenyi (Environmental earth sciences, 2024)
The strength reduction method (SRM) based on the generalized Hoek‒Brown (GHB) criterion has become an important and popular topic to analyse the stability of rock slopes. Various reduction strategies have been proposed and applied by the civil and mining engineering community. This paper proposed a new SRM for rock slopes with the GHB criterion based on the critical failure state curve (CFSC). The existence of the CFSC has been proven by theoretical analysis, and the explicit expression of the CFSCs for different parameters m i and slope angles β, considering the influence of disturbance factor D, has been obtained by curve fitting based on a great deal of simulation data. The new SRM provides a graphic method to determine the parameters at the critical failure state from the initial state by reducing the compressive strength of intact rock σ ci and the parameter combination s α with the same ratio and proposes a definition of the factor of safety (FOS) based on the parameters of the two states. This method was applied to nine slope examples to verify its validity and accuracy. The relative errors between the critical state parameters obtained from the graphic method and that from the simulation analysis are less than 10%, which proves the accuracy of the CFSCs. The FOSs obtained by the proposed definition are compared with those obtained by the Bishop simplified method and the local linearization method (LLM), and the results are very close. The relative error is less than ± 5% compared with the LLM, and the stability state predicted is perfectly accurate. However, the calculation procedure is largely simplified, and the calculation speed is largely improved. A practical case of an open pit limestone slope with multiple steps was detailed analysed by the proposed SRM based on CFSC. The FOS results comparison with other existing method has demonstrated its feasibility and reliability in engineering application.